Narsisme Agama dan Distorsi Ruang Publik: Analisis Perspektif Jürgen Habermas dalam Konteks Indonesia - Herrio Tekdi Nainggolan; Andrianus Nababan; Resmi Hutasoit (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to explore how religious narcissism shapes socio-religious behavioral patterns within society and to provide an overview of the expanding phenomenon through the relevance of Jürgen Habermas’s public sphere theory in the Indonesian religious context. This research employs a qualitative method using a literature study approach supported by netnographic methods. The findings reveal that religious narcissism within the public sphere is manifested through the use of religious symbols, narratives, and performative practices in both social and digital spaces as instruments of image construction, identity legitimization, and contestation among religious groups. This phenomenon is influenced by identity politics, majority logic, and the legacy of religious conflicts, all of which contribute to the distortion of the public sphere as conceptualized by Habermas. Religious narcissism not only reinforces social polarization and religious exclusivism, but also weakens tolerance, intensifies intolerance, and hinders efforts toward religious moderation and social cohesion in Indonesia.